Green Synthesis of CaO Nanoparticle from Chicken Eggshell using Lemongrass Leaf Water Extract - Gladys Ayu Paramita Kusumah Wardhani; Nina Ariesta (Jurnal Sains dan Terapan Kimia, 2025)
Sources of CaO in the synthesis of nanoparticles can be available from waste such as eggshell waste which has an average CaCO3 content of 94%. The study aimed to synthesize nanoparticles with various compositions of CaO-0 and CaO-1  (50 : 50) yielded from chicken egg shells mediated by extracts Cymbopogon citratus leaves and characterized the nanoparticles. Based on the results of phytochemical screening, Cymbopogon citratus extract contained alkaloids, flavonoids, triterpenoids, and tannins. The results of characterization with UV-Vis spectrophotometer showed that CaO was formed at the highest wavelength with a composition of CaO-1 (50 : 50) with a value of 250-300 nm. Absorption band of FT-IR spectra at wave numbers 428 cm-1 and 711 cm-1, it’s indicate of Ca-O vibrational band and Ca-O bonds, respectively. The particle size of crystalline CaO-0 based on calculations using the Debye Scherrer formula ranged from 33.72 - 38.48 nm while the particle size of crystalline CaO-1 ranged from 28.93 - 70.75 nm with diposide and calcite phases based on XRD data. The surface morphology using SEM shown that CaO-0 was shaped like an irregular cube while CaO-1 forms irregular spherical lumps. Keywords: CaO, green synthesis, Cymbopogon citratus, nanoparticle .